Androgen receptor polyglutamine repeat length (AR‐CAGn) modulates the effect of testosterone on androgen‐associated somatic traits in Filipino young adult men. Issue 2 (14th March 2017) - Ryan, Calen P.; Georgiev, Alexander V.; McDade, Thomas W.; Gettler, Lee T.; Eisenberg, Dan T. A.; Rzhetskaya, Margarita; Agustin, Sonny S.; Hayes, M. Geoffrey; Kuzawa, Christopher W.
Abstract: Objectives: The androgen receptor (AR) mediates expression of androgen‐associated somatic traits such as muscle mass and strength. Within the human AR is a highly variable glutamine short‐tandem repeat (AR‐CAGn), and CAG repeat number has been inversely correlated to AR transcriptional activity in vitro . However, evidence for an attenuating effect of long AR‐CAGn on androgen‐associated somatic traits has been inconsistent in human populations. One possible explanation for this lack of consistency is that the effect of AR‐CAGn on AR bioactivity in target tissues likely varies in relation to circulating androgen levels. Materials and Methods: We tested whether relationships between AR‐CAGn and several androgen‐associated somatic traits (waist circumference, lean mass, arm muscle area, and grip strength) were modified by salivary (waking and pre‐bed) and circulating (total) testosterone (T) levels in young adult males living in metropolitan Cebu, Philippines ( n  = 675). Results: When men's waking T was low, they had a reduction in three out of four androgen‐associated somatic traits with lengthening AR‐CAGn ( p  <   .1), consistent with in vitro research. However, when waking T was high, we observed the opposite effect—lengthening AR‐CAGn was associated with an increase in these same somatic traits. Discussion: Our finding that longer AR‐CAGn predicts greater androgen‐associated trait expression among high‐T men runs counter to in vitro work, but is generally consistent with the few prior studies to evaluate similar interactions in human populations. Collectively, these results raise questions about the applicability of findings derived from in vitro AR‐CAGn studies to the receptor's role in maintaining androgen‐associated somatic traits in human populations.